2013
DOI: 10.2108/zsj.30.877
|View full text |Cite
|
Sign up to set email alerts
|

An In-silico Genomic Survey to Annotate Genes Coding for Early Development-Relevant Signaling Molecules in the Pearl Oyster, Pinctada fucata

Abstract: The pearl oyster Pinctada fucata has great potential as a model system for lophotrochozoan developmental biology research. Pinctada fucata is an important commercial resource, and a significant body of primary research on this species has emphasized its basic aquaculture biology such as larval biology and growth, aquaculture, pearl formation and quality improvement, shell formation, and biomineralization. Recently, a draft genome sequence of this species was published, and many experimental resources are curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Finally, signal pathways related to mineralization, especially growth factors (GFs) and their receptors, despite the limitations of studies on invertebrate species, were studied in this project. Limited information about these cellular regulators during mineralization has been obtained from sequence analysis, [ 68 ] genomic survey, [ 69 ] and in vivo and in vitro studies. [ 70 ] However, these analogues were hypothesized to have a potential use in the regeneration of living bone for potential clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, signal pathways related to mineralization, especially growth factors (GFs) and their receptors, despite the limitations of studies on invertebrate species, were studied in this project. Limited information about these cellular regulators during mineralization has been obtained from sequence analysis, [ 68 ] genomic survey, [ 69 ] and in vivo and in vitro studies. [ 70 ] However, these analogues were hypothesized to have a potential use in the regeneration of living bone for potential clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…We identified two Hox genes, Hox5 and Hox3 (Figure 9), which are highly expressed in D-shaped veliger, indicating that they are involved in the growth of D-shaped larvae. We also found early developmentally relevant signaling molecules such as Hedghog, TGF β , and Wnt family, which are known to play important roles in axis formation, muscle differentiation, and nervous system development [26]. Recent evidence has suggested that classic morphogens, such as Wnts, TGF β /BMP family members, and Hedgehogs, may all serve as axon guidance cues for a variety of axons in different organisms [44].…”
Section: Discussionmentioning
confidence: 99%
“…For P. fucata , the draft genome [19] and tissue transcriptomes [2023] have been recently reported. Based on the transcriptomic sequences from a mixture of nine developmental stages of P. fucata [19], biomineralization-related gene expression profiles during larval development have been investigated [24, 25] and genes involved in body patterning [26], transcription factors [27], and homeobox genes [28] have been identified. Nonetheless, developmentally important genes and their expression patterns during the larval stages of developing P. fucata have not been systematically studied at the transcript level to date.…”
Section: Introductionmentioning
confidence: 99%
“…C. teleta embryos were fixed and WMISH was performed as previously described 152 . Capitella teleta orthologs Ct-fgf8/17/18/24 153 (Protein ID: 218971), Ct-pvf1 154 (Protein ID: 153454) and Ct-pvf2 154 (Protein ID: 220370) were mined from the publicly available genome 50 . WMISH samples were imaged on a Leica DMRA2 compound microscope coupled with a QIClick camera.…”
Section: Gene Expression Analysesmentioning
confidence: 99%